Effect of Feeding Different Levels of Rice Distillers Dried Grains with Soluble (RDDGS) on Performance of Broiler - Singh, Niharika; Dubey, Meenu; Doneria, Raina; Gendley, M. K.; Dinani, O. P.; Ramteke, R. C. (Indian Journal of Animal Nutrition, 2020)
Rice distillers dried grains with solubles (DDGS) is a co-product of rice-based ethanol production that can be a valuable source of energy, digestible amino acids, and available phosphorus in poultry feeds. Thus the present study was conducted for 5 weeks to study the effect of different dietary inclusion levels of rice DDGS on performance of broiler chickens. The diets were prepared using conventional feed ingredients: maize, deoiled soybean cakes, soy oil, rice DDGS and premixes containingtrace minerals and vitamins. The average body weight of chicks at the end of pre starter and starter phase was significantly (P